The comparison of performance of bidboland gas refinery unit based on the current designing and the new designing - Darabi, Mohsen; Mohammadiun, Mohammad; Mohammadiun, Hamid; Mortazavi, Saeed (International Journal of Scientific World, 2015)
One of the problems of Bidboland Gas Refinery especially in the cold seasons is the low temperature of the sour gas entering to Gas Refinement Unit that .This problem has a direct influence on output reduction of Amin-Amin Exchanger leading to an increase in gas fuel consumption in the Reboiler of Amin Recovery Tower because Amin-Amin exchanger is not able ,in the current condition ,to warm up Rich DEA solution to optimum temperature based on design of the manufacturer company .In order to solve this problem, the Amin-Amin exchanger was redesign by use of Aspen Hysys specialized software and it was used in the process by use of the Aspen Hysys software .Based on the obtained results, in case of using the new exchanger ,the Rich DEA solution temperature will increase from 33°C to 98°C that this increase in temperature causes a 33.2% reduction in gas consumption in the Reboiler. On the other hand ,as a result of improvement in the heat exchanging between Lean and Rich solutions ,temperature of the saturated Amin solution reduces to 57°C which, consequently there is no need to use air cooler to cool running Amin. These equipments are totally omitted from the process, and its operating costs will are returned to Bidboland Gas Refinery .Finally, it was revealed that using the new heat exchanger causes a capital-return to 114864 $ annually as a result of reducing energy consumption in Reboiler and air cooler.